Report on the Excavation of the Prehistoric, Roman, and post-Roman Site in Lydney Park, Gloucestershire - Wheeler, R.E.M (Reports of the Research Committee of the Society of Antiquaries of London, 1932)
This book reports on excavations on the Camp Hill promontory fort at Lydney, Gloucestershire, undertaken by Mortimer and Tessa Wheeler in 1928-9. The hillfort was established shortly before the first century BC. During the second and third centuries AD it was occupied by a Romano-British population engaged, at least partly, in iron mining. Excavations focussed on a temple, dedicated to the god Nodens, built within the fort, and associated with this were a guest house (mansion), baths and other structures. Structural details of these buildings are described, and specialist reports describe the worked stones, metalwork, pottery and other finds, recovered by the fieldwork.